Preliminary feasibility for public research & development projects - Yoon, Donghun (Emerald points., 2021)
Research and development infrastructures are a critical success factor in the platform of science and technology. In turn, an R&D preliminary feasibility study is essential to establish fairness and social credibility of a plan, including expert review, information disclosure and alternative setting. Preliminary Feasibility for Public Research & Development Projects explains how to evaluate R&D business by exploring the five key features of policy implication, policy improvement, preliminary feasibility study, R&D evaluation, and R&D strategy. Presenting policy measures to ensure the sustainability of R&D projects, Preliminary Feasibility for Public Research & Development Projects will help develop strategic measures for R&D preliminary feasibility studies while proposing ways to enhance the effectiveness of these studies, promote efficiency in public investment projects, and enhance the financial efficiency of large investment projects.